Non-Image Forming Effects of Light on Brainwaves, Autonomic Nervous Activity, Fatigue, and Performance. (12th September 2018) - Askaripoor, Taleb; Motamedzadeh, Majid; Golmohammadi, Rostam; Farhadian, Maryam; Babamiri, Mohammad; Samavati, Mehdi
Fatigue and sleepiness are one of the main causes of human errors and accidents in the workplace. The empirical evidence has approved that, in addition to stimulating the visual system, light elicits brain responses, which affect physiological and neurobehavioral human functions, known as the non-image forming (NIF) effects of light. As recent evidences have shown the positive effects of red or low correlated color temperature white light on alertness and performance, we investigated whether exposure to 2564 K light could improve subjective and objective measures of alertness and performance compared with 7343 K, 3730 K, and dim light (DL) conditions during the daytime. Twenty two healthy participants were exposed to the light while they were performing a sustained attention task and their electroencephalogram (EEG) and electrocardiogram (ECG) were recorded. Both 2564 K and 7343 K conditions significantly reduced EEG alpha-power compared with the DL and 3730 K conditions. Moreover, the 2564 K, 7343 K, and 3730 K conditions significantly reduced subjective fatigue, sleepiness and increased heart rate and performance compared with the DL condition. Furthermore, the effects of light conditions on alertness and performance varied over the day so that more effective responses were observed during the afternoon hours. These findings suggest that light interventions can be applied to improve daytime performance.